Vorschlag als Sprachhandlungsmuster: Methodologie der kontrastiven Analyse am Beispiel des deutsch-polnischen Sprachvergleichs - Elizaveta Kotorova; Tadeusz Zuchewicz (Beiträge zur Allgemeinen und Vergleichenden Sprachwissenschaft)
The present paper aims to describe the speech behaviour pattern of PROPOSAL in German and Polish. The term “speech behaviour pattern” refers to the purposeful verbal behaviour. The illocutionary content of PROPOSAL is determined in accordance with the theory of semantic primes. The contrastive analysis has the following three aspects. First, typical implementation forms of this speech behaviour pattern are described in both languages. Then, their use in concrete functional and communicative contexts is exemplified. Finally, the composition of the communicative-pragmatic field of PROPOSAL is analysed in German and Polish. Particular attention is given to the central and peripheral forms of implementation as well as to the similarities and differences in the formulation of utterances expressing PROPOSAL in German and Polish.